Are we one and the same? : scholarly representation of gender in Sami reindeer herding - Bellis, Dana (Universitetet i Tromsø, 2010)
This thesis focuses on representations of gender in Sami reindeer herding in West Finnmark, Norway. I analyze to what extent are scholarly representations of gender accurate when compared to the local experience of modernization, by focusing on masculinity. This analysis builds on the history of Norwegian reindeer herding regulations from the Lapp Codicil to recent debates on the amendments to the 1978 Reindeer Herding Act to determine when and why gender has become a topic of concern. Mechanization’s impact on gendered participation and representation is analyzed by determining to what extent early ethnographic works contributed to the masculinization of reindeer herding. This is contrasted against local narratives that demonstrate how modernizing transportation was adapted in the family and siida differently than described by scholars. Analyzing the relationship between regulations and gendered representation in reindeer herding will argue that current gender discussions have marginalized the gendered experience of men.